Pengaruh Kualitas Pelayanan terhadap Kepuasan Nasabah Kredit Cepat Aman (KCA) (Studi Kasus pada Perum Pegadaian di Makassar) - Nursyamsi, Idayanti (Jurnal Aplikasi Manajemen, 2009)
The aim of the study was analyzed the effect of service quality to customer satisfaction, such as tangible, responsiveness, reability, assurance, and emphaty on the KCA at Perum Pegadaian on Makassar and the most dominant dimension affected the customers' satisfaction. The analysis used at this research used multiple linear regression. The result of the study indicated that the service quality have positive and significant to influenced on the customers' satisfaction. The most dominant affected the customers' satisfaction was tangible.